Acute myocardial infarction in a young woman with severe ulcerative colitis - (:unkn) unknown (ELSEVIER IRELAND LTD, 2002)
In this report we present a case of a 28-year-old woman who was admitted to our emergency room complaining of chest pain. Her clinical ECG and biochemical evaluation was consistent with acute nonatherogenic myocardial infarction. Subsequent work is revealed that she was suffering from ulcerative colitis with acute exacerbation since last week. We discussed triggering factors for thrombogenic and inflammatory tendency of patient with comprehensive review of literature to clarify the causal relationship. (C) 2002 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: acute myocardial infarction; ulcerative colitis; thromboembolic disease